Development and validation of sampling plans for Frankliniella schultzei on tomato. (August 2020) - Araújo, Tamíris A. de; Pezzini, Daniela T.; Ramos, Rodrigo S.; Picanço, Marcelo C.; Bastos, Cristina S.; Hunt, Thomas E.; Hutchison, William D.
Abstract: Tomato is known to be among the most affected crops for several Frankliniella schultzei transmitted tospoviruses that cause extensive economic losses worldwide. Despite the importance of this insect as a vector in tomato, no research-based economic thresholds or sampling plans have been developed for use in integrated pest management (IPM) programs for this pest on tomato. Here, six sampling schemes and the sampling distribution of F. schultzei on tomato were investigated. We also developed and evaluated eight sampling plans for F. schultzei on tomato using nominal thresholds, numerous field data sets and computer simulation. Beating the tomato plant apical section over a white plastic tray was the best sampling method to assess F. schultzei density. In addition, F. schultzei had an aggregated sampling distribution in tomato fields. Both sequential and conventional plans resulted in similar decision-making outcomes; however, depending on the nominal threshold adopted, the economy of time when using the sequential sampling plans in relation to conventional sampling plans ranged from 30% to 80%. The beating tray sampling method used in this study provided the best accuracy and was most cost-effective for F. schultzei sampling. The nominal thresholds associated with the binomial sequential sampling plans developed are an efficient and time-saving option for managing F. schultzei and the associated tospovirus complex in tomato, contributing toward improved integrated pest management programs for this economic pest of tomato. Graphical abstract: Image 1 Highlights: Decision-making system for Frankliniella schultzei in tomato crops. Beating the tomato plant apical section over a white plastic tray was the best sampling system to assess F. schultzei. Frankliniella schultzei has aggregated sampling distribution on tomato fields. Nominal thresholds associated with the sequential sampling plans provide a reduction of the sampling effort of  F. schultzei .